Jobsite [videorecording (DVD)] : concrete countdown. (A & E Home Video, 2011)
Watch as a crew of 350 construction workers attempt to pour the top floor of a skyscraper in the middle of Manhattan, in less than 90 minutes. From the second water is added to the concrete mix, its already starting to harden and if it doesn't make it from the plant to the site, reach the 60th floor, get poured and smoothed out all in 90 minutes, it's useless and a day of work is lost.